Understanding of eco-shaming phenomena in Kazakhstan - Kumambetova, Nina (2021)
This paper aims to analyse how eco-shaming practices are being understood by environmental activists and people actively involved in Kazakhstan's ecological agenda. Although there have been many studies on how receivers of eco-shaming artifacts react to them, there is a gap in how environmental communication campaign producers use the knowledge about eco-shaming and what language they elaborate on and think about eco-shaming. This study will allow a better understanding of what environmental communication practitioners need in terms of assessment and reflection in order to consider when and how to use eco-shaming to strive for changes and when not.